IMPLEMENTASI PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER KRISTIANI PESERTA DIDIK DI LINGKUNGAN SEKOLAH - Rismayanti; Elsya Stefanne Salleppa; Imelda Rapa' Langi'; Priskilya Desmiati Sorreng (CV. ADIBA AISHA AMIRA, 2026)
Christian Religious Education plays a crucial role in shaping the Christian character of students in the school environment. This study aims to examine how the implementation of Christian Religious Education shapes students' character through the learning process, teacher role models, and school environmental support. This study uses a qualitative approach with descriptive methods to obtain an in-depth overview of character education practices in Christian Religious Education learning. Data collection techniques were carried out through observation, interviews, and documentation of learning activities and interactions in the school environment. The results of the study indicate that the formation of students' Christian character is influenced by several important factors, namely the role of teachers as role models, the application of contextual and reflective learning strategies, and a school culture that supports the values ​​of love, honesty, responsibility, and concern for others. Thus, the integrated implementation of Christian Religious Education can be an effective means of building the character of students who are faithful and have integrity in their personal and social lives.